Imperial citizenship : empire and the question of belonging - Gorman, Daniel, 1974- (Studies in imperialism., 2006)
This is the first book-length study of the ideological foundations of British imperialism in the early twentieth century. By focusing on the concept of imperial citizenship, the book illustrates how the political, cultural and intellectual underpinnings of Empire were constructed and challenged by forces in both Britain and the 'Britons overseas', in the settlement colonies of Canada, South Africa, New Zealand and Australia. Debates about imperial citizenship reveal how Britons conceived the Empire: was it an extension of the nation-state, a collection of separate and distinct communities, or a type of 'world state'? These debates also discussed the place of Empire in British society, its importance to the national identity and the degree to which imperial subjects were or were not seen as 'fellow Britons'. This public discourse was at its most fervent from the South African War (1899-1902) to the early 1920s, when Britain emerged victorious, shocked and exhausted from the Great War.--Book jacket.